A DIGITAL ADAPTIVE TEXTBOOK FOR SECONDARY BIOLOGY EDUCATION: DEVELOPMENT AND TESTING: Received: 12th March 2026, Revised: 22th April 2026, Accepted: 05th May 2026, Date of Publication: 12th June 2026 - Boris Yarmakhov; Sergey Sumatokhin (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The digital transformation of educational materials has led to the development of adaptive textbooks that personalize learning according to individual student needs. This paper presents the development and pilot testing of an adaptive digital biology textbook (TSAU) for middle school students in Russia, based on the printed textbook by V. Pasechnik. The research aimed to transform traditional content into an adaptive digital format and evaluate its effectiveness in improving student academic performance. The digital textbook comprises 110 multimedia modules, each containing a video clip and six assessment tasks of varying difficulty levels. The adaptive platform processes student responses, provides immediate feedback, and creates individualized learning paths based on student progress. The study concludes that the adaptive digital textbook significantly enhances biology instruction quality by promoting comprehensive material coverage, providing differentiated assignments, and increasing student engagement. The findings suggest that adaptive learning technologies can effectively support personalized education and improve academic outcomes in secondary school settings.